المقامية بين مفهومي الانسجام والتداولية قصيدة الفردوس المفقود لأبي البقاء الرندي "أنموذجا" - بلهادي, مشانة, مروة حليمة (جامعة الوادي university of eloued, 2018)
الملخص: هدفت الدراسة إلى الكشف عن العناصر المقامية المشتركة بين كل من الانسجام والتداولية، من خلال ابراز دور الانسجام والتداولية في الكشف عن المقامية في قصيدة، وذلك عن طريق تطبيق آليات الانسجام من منظور بروان ويول على قصيدة الفردوس المفقودة لأبي البقاء الذي بدء بالسياق والتأويل المحلي ومبدأ التشابه والتفريض، وبيان علاقاتها بالسياق المقامي، ومن خلال التحليل تبين أن مقاربة بروان ويول تركز على أن الانسجام هو القراءة الانتاجية للنص، كما أنه قائم المقام الذي يحدث فن الخطاب، ومبدأ التغريض. يركز على عناصر السياق المقامي المتمثلة في الاحالات التي تحيل إلى المكان والزمان والشخوص. أمّا مبدأ التشابه، قائم على الربط بين النص الحاضر والمعرفة الخلفية الحاضرة بذهن المتلقي. أمّا التداولية فكانت من خلال تطبيق أهم مبادئها على قصيدة الفردوس المفقود لأبي البقاء الرندي مركزين على الإشاريات والأفعال الكلامية ومتضمنات القول وبيان علاقتها بالسياق المقامي حيث ساهمت الإشاريات في القصيدة على: تأسيس العلاقة الشخصيّة التي بينت أهم الأشخاص الذين تدور حولهم القصيدة المرتبطة بالإحالات النصيّة والمقاميـّة؛ الواضحة في الضميرين "أنتم ونا" كما أن الإشاريّات الزمانيّة ارتبطت بسياق التلفظي، أما الإشاريات المكانيّة حددت مكان الحدث المتناسب مع القصيدة. ويظهر دور الإشاريات الاجتماعيّة في بروز العلاقة القائمة بين الألفاظ الموظفة في القصيدة وموضوعها، غلبة الأفعال غير المباشرة على المباشرة، لأنها تعتمد على التأويل من خلال بروز الأفعال التعبيريّة التي عبر بها عن مأساة الاندلس بألفاظ معبرة على شدة الحزن، والأفعال الإخباريّة المتناسبة مع السياق، و التوجيهيّة المرتبطة ضمنيّا بالتقرير والإثبات؛ كما تضمنت مجموعة من الارشادات وتحذيرات وأوامر مباشرة. أما علاقة متضمنات القول بالسياق المقامي تكمن في علاقة الافتراض المسبق بالأحداث التي حصلت في بلاد الاندلس وكذا الأقوال المضمرة فلا تتحدد دلالة الكلمة الا من خلال السياق. ومن أهم النقاط المشتركة بين الانسجام والتداولية، الإشاريات بأنواعها، الشخصية والزمانية والمكانية؛ باعتبارها عناصر مهمة في السياق المقامي والمتجسدة في عناصر التأويل المحلي. Résumé : فرنسية أو انجلزية The study aimed at uncovering the common denominational elements of both harmony and deliberation, by highlighting the role of harmony and deliberation in revealing the sanctuary in a poem, by applying the mechanisms of harmony from the perspective of Brown and the poem on Paradise Lost to the father of survival, which started with context and local interpretation and the principle of similarity And the relationship between the context and the context. The analysis shows that the approach of Brown and Yole emphasizes that harmony is the productive reading of the text, as it is the place where the art of speech occurs and the principle of degeneration. Focuses on the elements of the context of representations that refer to place, time and characters. The principle of similarity is based on the connection between the present text and the background knowledge present in the recipient's mind. The deliberation was through the application of the most important principles on the poem Paradise Lost to the father of survival Rundi centers on the references and verbal actions and implications of the statement and its relationship to the context of the place where the references in the poem contributed to: Establishing the personal relationship that showed the most important people around whom the poem is connected with textual and explicit references; in the two pronouns "you and us" and the temporal references were associated with the context of the text, whereas the spatial references determined the place of the event proportional to the poem. The role of social references in the emergence of the relationship between the words employed in the poem and its theme, the predominance of indirect acts on the direct, is based on the interpretation of the expression of the expression of the tragedy of Andalusia with expressions of sadness, The guidelines implicitly associated with the report and evidence; and included a series of direct instructions, warnings and orders. The relationship of the implications of the contextual context lies in the relationship of the presupposition of the events that took place in the country of Andalusia as well as the quotations. The meaning of the word is determined only through the context. Among the most common points of harmony and deliberation are the various types of personal, temporal and spatial references; they are important elements in the context of localization and are embodied in the elements of local interpretation.
Keywords: المقامية – التداولية – لسانيات النص – السياق المقامي – الانسجام - النصية; Grammar, grammar, sentence structure and / or amend sensitive content.